A platform for long-term monitoring the deep brain rhythms. (13th January 2017) - Qian, Xing; Chen, Yue; Feng, Yuan; Ma, Bozhi; Hao, Hongwei; Li, Luming
Abstract: Deep brain stimulation (DBS) provides a valuable platform for recording local field potentials (LFP) during surgery for studying the mechanisms of brain diseases and DBS therapy. Long-term neural activity monitoring remains a necessity for research on some neurodegenerative disorders and closed-loop DBS systems. A neurostimulator with recording ability has been developed as a research tool and a medical device. This study investigates the feasibility of chronic electrophysiological studies using neurostimulator (model G102RS) for recording LFP. Recent studies have suggested that oscillatory beta band activity can be used as a biomarker of Parkinson's disease (PD). Here, subthalamic LFP recordings were obtained from (i) a group of PD patients undergoing DBS therapy, (ii) the1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP) lesioned monkey model of PD, and (iii) a PD patient with an implanted neurostimulator. A total of 55/60 LFP datasets measured from the PD patients at rest during the operation contained spectral peaks in beta band as pathophysiological oscillations. These oscillations were strongly suppressed during DBS. The long-term animal experiment and the clinical implant demonstrated that the G102RS can adequately record the long-term frequency band-specific amplitude fluctuations such as the beta band activity. The device could identify the suppression of the beta band activity during DBS. Together, these data demonstrate the use of this medical device for chronic electrophysiological studies.